Analysis of liquid rocket propellant in nitroglycerin injector reactors - maryono maryono; Muhammad Akhlis Rizza (Jurnal POLIMESIN, 2023)
The propulsion of the rocket is due to the thrust resulting from the combustion rate. The propellant energy can be increased by increasing the fuel pressure and temperature of the propellant. Increasing the pressure and temperature of the propellant will increase its combustion rate and the operating conditions of the rocket motor. The most effective liquid propellant used is Nitroglycerin (NG). Nitroglycerin was prepared using the glycerol nitration method with the principle of an injector-based reactor. Therefore, in this research, nitroglycerin was made using the Injector Reactor method with variations in flow rate and injection volume. The results showed that the effect of variations in flow rate and solution volume on the synthesis of nitroglycerin caused a change in solution temperature. Flow rate is closely related to the volume of solution used. The higher the temperature produced, the more heat energy will increase so that the pressure and combustion rate of the propellant increase. The most optimum results use a flow rate of 200 µm/s and a solution volume of 6 ml of glycerin, nitric acid, and sulfuric acid each with a temperature of 37.6oC.